2004
DOI: 10.1111/j.0019-2805.2004.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiling of leprosy and tuberculosis patients to 15‐mer peptides of Mycobacterium leprae and M. tuberculosis GroES in a BCG vaccinated area: implications for development of vaccine and diagnostic reagents

Abstract: SUMMARYMycobacterium leprae (ML) GroES has been shown to induce strong T cell responses in tuberculoid as well as in exposed healthy contacts of leprosy patients, and therefore this antigen has been the focus of study as a potential vaccine candidate. Paradoxically, we have shown that ML GroES also induces extremely high titres of IgG1 antibody in leprosy patients across the disease spectrum, a response associated with disease progression. IgG1 antibodies in leprosy also show a negative association with interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…Our results are correlating with earlier publications and many of the proteins identified in the PPD of M. tuberculosis , have already been analyzed for their potential as a diagnostic markers. Some of the hits we have found are GroES [52,53], GroEL [54,55], protein EsxB (EsxB) [56] heat shock protein HspX (HspX) [57], hypothetical protein (TB15.3), hypothetical protien (TB16.3) [58], 50S ribosomal protein L7/L12 (RplL) [59], hypothetical protein (EsxA) [60], immunogenic protein Mpt63 (Mpt63) [61], Mpt64 [62], ESAT-6 like protein EsxJ (EsxJ), and ESAT-6 like protein EsxO (EsxO) [63]. Based on these observations, many more M. tuberculosis PPD can be analyzed and the abundant antigens be evaluated for their potential as diagnostics biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are correlating with earlier publications and many of the proteins identified in the PPD of M. tuberculosis , have already been analyzed for their potential as a diagnostic markers. Some of the hits we have found are GroES [52,53], GroEL [54,55], protein EsxB (EsxB) [56] heat shock protein HspX (HspX) [57], hypothetical protein (TB15.3), hypothetical protien (TB16.3) [58], 50S ribosomal protein L7/L12 (RplL) [59], hypothetical protein (EsxA) [60], immunogenic protein Mpt63 (Mpt63) [61], Mpt64 [62], ESAT-6 like protein EsxJ (EsxJ), and ESAT-6 like protein EsxO (EsxO) [63]. Based on these observations, many more M. tuberculosis PPD can be analyzed and the abundant antigens be evaluated for their potential as diagnostics biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-␣), a proinflammatory cytokine, is also required for control of the infection, as shown by the increased incidence of TB reactivation in individuals receiving anti-TNF-␣ antibody treatment for unrelated disease. Other examples of proinflammatory responses are the production of IL-2, which is involved in the clonal expansion of antigen-specific T cells (125), and of the chemokine CXCL10 (IP-10), which is important in trafficking monocytes and Th1 cells to the site of (90) (32,67,140). For example, the presence of IFN-␥ favors IgG2, IL-4 and IL-13 favor IgG4, while IL-10 favors IgG1 and IgG3.…”
Section: Mediators Of Antigen-specific Immune Responsesmentioning
confidence: 99%
“…The literature and our study show that the low sensitivity of IGRA to current peptide antigens may be attributable to low antigen availability and poor T cell recognition of the parent proteins by the host immune system. A number of well-known M. leprae antigens (MMPI, MMPII, GroES, ML0049, and ML0050) induce strong cell-mediated and humoral immune responses in leprosy patients (24,(34)(35)(36)(37)(38). Araoz et al (6,7) showed that a few of the recombinant hypothetical unknown proteins can be recognized by circulating antibodies in sera of leprosy patients but also induce M. leprae-specific T cell responses in leprosy and endemic control populations.…”
Section: Discussionmentioning
confidence: 99%